Revalidation of Pyxicephalus angusticeps Parry, 1982 (Anura: Natatanura: Pyxicephalidae), a bullfrog endemic to the lowlands of eastern Africa - Scott, Elizabeth; Visser, John D.; Yetman, Caroline A.; Yetman, Caroline A.; Oliver, Lauren; Broadley, Donald G. (Zootaxa, 2013)
Pyxicephalus currently contains three recognized species, viz. P. adspersus, P. edulis and P. obbianus, the former two of which have a long history of confusion. Parry (1982) described P. adspersus angusticeps from Beira, Mozambique, which was synonymized with P. edulis. We re-examine the taxonomic status of Pyxicephalus taxa from Mozambique, examining the types and contrasting them to congeners throughout Africa. Morphological characters previously used to delimit species in Pyxicephalus are examined, and problems with some identified. Additional diagnostic characters and their variation in Pyxicephalus are discussed, and a revised key is provided. Confusion among species in the genus, type localities, literature and folklore led to P. adspersus angusticeps being incorrectly synonymized with P. edulis. We formally revalidate P. angusticeps, and designate a lectotype for P. edulis. The identity of voucher specimens from previous work suggests that the breeding ecology of P. angusticeps is distinct from that of P. adspersus and P. edulis, and that the advertisement call of P. angusticeps was used as part of the evidence for elevating P. edulis out of synonymy with P. adspersus. The previous confusion of P. adspersus and P. edulis does not affect the recognition of P. angusticeps. The wider implication of the previous misidentification of P. angusticeps as P. edulis is that most of the museum material labeled as P. adspersus from East Africa is P. edulis, and most of the museum material labeled as P. edulis from East Africa is P. angusticeps. This conclusion has been confirmed from East African museum material thus far examined.